A review study of targeting of AAK1 and JAK1/2 using baricitinib in COVID-19 infected human cells - Al-Humaidhi, Abeer M (AL-Kindy College Medical Journal, 2020)
The outbreak of a current public health coronavirus 2019 disease is a causative agent of a serious acute respiratory syndrome and even death. COVID-19 has exposed to multi-suggested pharmaceutical agents to control this global disease. Baricitinib, a well-known antirheumatic agent, was one of them. This article reviews the likely pros and cons of baricitinib in attenuation of COVID-19 based on the mechanism of drug action as well as its pharmacokinetics. The inhibitory effect of baricitinib on receptor mediated endocytosis promoter, AKK1, and on JAK-STAT signaling pathway is benefacial in inhibition of both viral assembling and inflammation. Also, its pharmacokinetic has encouraged the physicians toward the drug selection for COVID-19 treatment. On the other hand, most of baricitinib side effects are dose-dependent. In conclusion, targeting of AAK1 and JAK1/2 using baricitinib has predicted to be potential and effective with minimal side effects in management COVID-19 infected patients for a short therapeutic dosing period. Laboratory monitoring should be considered for some parameters. However, experimental trials are mandatory for a long-term treatment with a lower dose of baricitinib to evaluate its effectiveness and safety in patients with moderate COVID-19 infection.